Self-Propelled Jump Regime in Nanoscale Droplet Collisions: A Molecular Dynamics Study (Communications in Computational Physics, 2020)
Self-propelled jump of droplets is among the most striking phenomena indroplet collisions on substrates. Self-propelled jump phenomena of droplets have beenobserved in experiments, which have also been reproduced in macro- or mesoscalenumerical simulations. However, there have been few previous studies on the phenomenaat nanoscales. To unravel the dynamics and mechanisms of nanoscale binarydroplet collisions on substrates, head-on collision processes of two identical waterdroplets with diameters of 10nm on graphite substrates are investigated by moleculardynamics (MD) simulations. By varying the impact Reynolds number of binarydroplet collisions on hydrophilic or hydrophobic substrates, we successfully reproduceself-propelled jump of droplets on a super-hydrophobic surface with a contactangle of 143◦ and a relatively high impact Reynolds number of 17.5. Parametric studiesindicate that both high impact Reynolds numbers and high hydrophobicity promoteself-propelled jump. Moreover, the criterion based on the Ohnesorge number derivedfrom the mesoscopic self-propelled jump regime is insufficient to precisely predict ananoscale self-propelled jump phenomenon. For this reason, our study includes theimpact Reynolds number and the substrate properties like contact angle as additionalcriteria to refine and extend the current theory for the self-propelled jump behavioursto nanoscales. The study provides insight into the mechanism of self-propelled jumpphenomenon at nanoscales.
Keywords: Self-propelled jump; binary droplet collision; hydrophobic substrates; molecular dynamics.